2001
DOI: 10.3923/pjbs.2001.351.355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Chloride Salinity on Seed Germination and Early Seedling Growth of Rice (Oryza sativa L.)

Abstract: Nipponbare (typical japonica type), Gorishita and Pangri (indica type; cultivated in the southern districts of Bangladesh) were compared with emphasis on seed germination and early seedling growth characters. Seeds were placed for germination and the seedlings were allowed to grow for 7 days at 0, 0.01, 0.03, 0.06 and 0.1% NaCI concentrations in water culture and for 14 days at 0, 0.1, 0.3, 1.0 and 3.0% NaCI concentrations in soil culture. Salinities up to 0.3% delayed germination but did not reduce final germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We observed that the effects of salinity on root length were more drastic than for shoot length. This difference might be due to the effect of NaCl being more inhibitory on root growth than shoot growth [70]. Moreover, the reduction in FW and DW may be due to the toxic effect of Na + on photosynthesis rate at higher concentrations [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the effects of salinity on root length were more drastic than for shoot length. This difference might be due to the effect of NaCl being more inhibitory on root growth than shoot growth [70]. Moreover, the reduction in FW and DW may be due to the toxic effect of Na + on photosynthesis rate at higher concentrations [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The foliar or soaking application of NPs-Si and NPs-Se has a favorable effect on the root length, root volume, and root thickness compared to the control treatment for both cultivars, particularly Giza 177. The reduction in the root length of plants grown in saline soil might be due to the high inhibitory effect of NaCl salt to root growth compared to that of shoot growth [ 49 ]. Excessive accumulation of Na + , Cl − , and SO 4 −2 ions in plant roots reduces the osmotic potential and limits water intake and plant growth, resulting in plant mortality in some situations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…When plants suffer from less nutrients and limited water availability, division of cells for the enlargement of shoot also become disturbed. Such conditions resulted in poor development of shoot length [ 48 ]. In addition, osmotic stress generated by higher concentration of salts also decreased the rate of seeds germination.…”
Section: Discussionmentioning
confidence: 99%